Stressors faced by university students and their coping strategies: a case study of Midlands State University students in Zimbabwe - Kasayira, Joseph M.; Chipandambira, Kudzai S.; Hungwe, Chipo (IEEE, 2014)
The study examined coping strategies used by students at a medium size developing country university. Participants constituted two hundred and eighty one Social Sciences students at the Midlands State University in Zimbabwe [49% female, 51% male]. A questionnaire was used to collect data. The results showed that the seven most common clusters of stressors were Finance, Library resources and study material, Accommodation, Food, Transport, Inadequate infrastructure and Lecturer related problems respectively. These stressors were rated as most common and most difficult by both sexes as well as by resident, non-resident students and students in different academic years. The students mentioned thirty-four coping strategies, which were divided into various categories. Strategies categorised under Direct positive coping strategies were considered to be the most effective while those categorised under Ad hoc coping strategies were considered least effective. Sex, residence status and academic year differences were evaluated using Mann Whitney U test and Kruskal-Wallis - rank order analysis of variance. There were no significant differences in the generic categories of coping strategies applied with respect to the three demographic variables. The findings of the study have implications on institutionalisation and strengthening of the student support system at state universities in Zimbabwe.